Kepuasan Pasien Stagnan di Instalasi Gawat Darurat (IGD) di Kupang - Nana Rochana; Noeh Nuwa Djogotuga (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: The quality of nursing services in the Emergency Department was greatly affected by the high number of stagnant patients resulting in their satisfaction. However, limited evidence was shown about the satisfaction level of stagnant patients in the Emergency Department in Indonesia. This study aims to know the satisfaction level of stagnant patients on the services in an Kupang Emergency Department. Methods: The total sample in this study was 109 respondents recruited by an accidental sampling method. Data were taken using a questionnaire of Brief Emergency Department Patient Satisfaction Scale (BEPSS); and analyzed using descriptive statistics (frequency and percentage). Results: The results of this study showed that as many as 89% of stagnant patients were satisfied with Emergency Department's services. The responsiveness dimension had the highest level of stagnant patient satisfaction (99.1%) compared to the tangible dimension (78.9%). The quality of service provided to stagnant patients in the emergency department should be improved especially on the tangible dimension though the majority of patients were happy with the service. Suggestion: This study suggests to the hospital to manage a comfortable ED surrounding to the patients.